IAS 37 and Financial Reporting Quality of Listed Oil and Gas Companies in Nigeria - Olorunfemi, Gbenga Samuel; Tunji, Siyanbola (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Financial reporting quality (FRQ) in Nigeria’s oil and gas sector has been undermined by weak disclosures, opaque recognition of provisions, and limited regulatory enforcement. This study examines the effect of IAS 37: Provisions, Contingent Liabilities, and Contingent Assets on FRQ among listed firms, using audited annual reports from 2020 to 2023. A mixed-method approach combining content analysis and panel regression was applied. The results show that both recognition compliance and disclosure quality significantly enhance FRQ, with disclosure quality exerting the stronger influence. Unlike previous Nigerian studies, this research develops a disclosure-based index of FRQ and integrates it with firm-level factors such as audit quality and leverage. The findings highlight the importance of robust enforcement, clearer disclosure practices, and high-quality audits in strengthening transparency and investor confidence in the extractive sector.